Strategi Mitigasi Bencana Alam Berbasis Masyarakat Di Daerah Rawan Gempa - Amelia, Riska; Saepudin, Eli Apud; Maharani, Putri Suci; Aprillianti, Rika; Ardiansyah, Syendy; Pajar, Nanda Putra (UNIVERSITAS SERAMBI MEKKAH, 2025)
In earthquake-affected areas, community-based disaster response strategies are an approach that requires communities to actively participate in actions to reduce the risk of potential earthquakes and improve preparedness plans. Earthquake-prone areas often face significant challenges in terms of vulnerability and disaster impact; Therefore, more sustainable and adaptable solutions are needed. A community-based approach builds disaster strategies based on the capabilities, knowledge, and participation of local communities. This includes forming a disaster response team, learning methods to reduce risk and learning how to build earthquake-resistant buildings. The study aims to identify the key components that influence the success of community-based disaster risk reduction in earthquake-prone areas and to assess how these factors affect disaster risk reduction.